An Addendum to the Chemiosmotic Theory of Mitochondrial Activity: The Role of RNA as a Proton Sink - Ramin M. Farahani (Biomolecules)
Mitochondrial ATP synthesis is driven by harnessing the electrochemical gradient of protons (proton motive force) across the mitochondrial inner membrane via the process of chemiosmosis. While there is consensus that the proton gradient is generated by components of the electron transport chain, the mechanism by which protons are supplied to ATP synthase remains controversial. As opposed to a global coupling model whereby protons diffuse into the intermembrane space, a localised coupling model predicts that protons remain closely associated with the lipid membrane prior to interaction with ATP synthase. Herein, a revised version of the chemiosmotic theory is proposed by introducing an RNA-based proton sink which aligns the release of sequestered protons to availability of ADP and Pi thereby maximising the efficiency of oxidative phosphorylation.